A note on the virulence study of Coniophora puteana (Schumacher ex Fries) Karsten, Gloeophyllum trabeum (Persoon ex Fries) Murrill and Postia Placenta (Fr.) M.J. Lars et Lomb on differents culture media - Troya, M. T.; Navarrete, A. (Forest Systems, 1992)
Fungi used for tests on fungicide effectiveness of wood preservatives can loose their virulence throughout time. This loss relates to the enzymatic inhibition produced in the successive mass transfers in artificial culture media. This work describes the methodology used to restore that virulence by growing the fungi in different culture media, with or without wood sawdust which can be later evaluated by the weight loss suffered by test specimens of Pinus sylvestris L.